Rate and Spraying Frequency Determination of Propiconazole Fungicide for the Management of Garlic Rust at Woreilu District, Northeastern Ethiopia - Admasie Kassaw; Aderajew Mihretie; Abebe Ayalew (Advances in Agriculture)
Rust is a major disease of garlic in Ethiopia. A field experiment was conducted at Kabe and Segno Kebeles of Woreilu District in 2019 to determine the appropriate rate and spraying frequency of propiconazole fungicide and select cost-effective management options of garlic rust. A randomized complete block design with three replications was used. The combination of five rates and three spraying frequencies of propiconazole fungicide and unsprayed treatments was evaluated. A combination of rate and spraying frequencies of propiconazole significantly reduced disease with correspondingly increased bulb yield of garlic. The minimum percentage severity index and area under disease progress curve were scored from plots treated by all rates with three times spraying frequency of Tilt fungicide application. The highest bulb yield was obtained from plots treated with all fungicide rates with three times spraying frequencies of propiconazole application. But the highest (6896.36%) marginal rate of return was obtained from plots treated with 0.5 L with two times spraying. Generally, 0.5 liters with two times spraying of propiconazole was effective in controlling garlic disease and get the highest cost-benefit advantage as compared with other treatments. Therefore, it could be recommended for the management of garlic rust in Ethiopia.